Association between maternal hemoglobin concentration and placental weight to birthweight ratio: The Japan Environment and Children's Study (JECS). (November 2020) - Mitsuda, Naomi; J-P, Naw Awn; Eitoku, Masamitsu; Maeda, Nagamasa; Fujieda, Mikiya; Suganuma, Narufumi; ,; Kamijima, Michihiro; Yamazaki, Shin; Kishi, Reiko; Yaegashi, Nobuo; Hashimoto, Koichi; et al.
Abstract: Introduction: Past studies have shown that maternal anemia is associated with a heavy placenta or a higher placental weight/birthweight (PW/BW) ratio. Although these findings suggest a non-linear relationship between maternal hemoglobin concentration and PW/BW ratio, this relationship has not been closely examined. Methods: We evaluated 83, 354 singletons and their mothers in a nation-wide birth cohort study, the Japan Environment and Children's Study (JECS). The associations between maternal hemoglobin concentration and placental weight, birthweight, and PW/BW ratio were assessed. Results: Mean placental weight was significantly higher in women with moderate or severe anemia (576 [183] g), but not in women with elevated hemoglobin levels (564 [117] g), compared with in women with normal hemoglobin levels (560 [115] g). In contrast, mean PW/BW ratio was significantly higher in women with moderate or severe anemia (0.190 [0.049]) or elevated hemoglobin levels (0.189 [0.033]) than in women with normal hemoglobin levels (0.185 [0.033]). In a regression analysis with cubic spline, a U-shaped relationship was found between maternal hemoglobin concentration and PW/BW ratio. Discussion: We demonstrated non-linear and concentration-dependent relationships between maternal hemoglobin concentration and placental weight, birthweight, and PW/BW ratio. Although the mechanisms underlying these associations are not fully understood, we suggest that low or elevated hemoglobin concentration may lead to placental compensatory hypertrophy and fetal growth restriction. Prevention and proper management of anemia before and during pregnancy are important for a well-functioning placenta and favorable fetal growth. Highlights: Maternal hemoglobin, placental weight, birthweight, and PW/BW ratio were examined. Placental weight was higher in anemic women than in women with normal hemoglobin. Birthweight was lower in women with elevated hemoglobin than in normal women. Impact of hemoglobin level on placental weight was greater in male offspring. PW/BW ratio showed a U-shaped relationship with maternal hemoglobin level.